TBH, too much drama - Greenwald, Lisa (Greenwald, Lisa. TBH, 2019)
Best friends Cecily, Gabby, and Prianka face drama in the last days of school as a meme goes viral, their mothers take them bra shopping together, and Cecily develops her first crush. Told entirely in text messages, emails, and notes.